Los procesos lectores de la Corporación Promotora Cívico Cultural Zuro Riente : una alternativa para disminuir la injusticia social (2017)
This research intends to understand the ways in which the reading processes developed by the ?Corporación Promotora Cívico Cultural Zuro Riente? influenced the formation of the subjectivity of a group of participants, and how those processes have been useful to reduce the levels of social injustice in the territory where they were implemented. In the first chapter the theoretical proposal Schema Criticism, developed by the North American researcher Mark Bracher, is exposed. It assures that the reading of literary texts is a useful tool to diminish the social injustice. In addition, the concepts "decoding", "deciphering" and "pleasure" are studied, based on the proposals of Estanislao Zuleta and William Ospina. These concepts are useful in suggesting a way through which the reader can approach a reading of literary texts in which the implementation of Schema Criticism is possible. The second chapter describes the reading processes developed by the aforementioned corporation. Then, based on a series of data collected through written interviews, surveys and film records, and based on the theoretical proposal of Bracher, the ways in which these reading processes influenced the formation of participants' subjectivity and the construction of social justice are established.--Tomado del Formato de Documento de Grado.